ANALYSIS OF MICROSOFT STREAM E-LEARNING FOR AUTOMOTIVE COMPANY EMPLOYEES USING THE UTAUT MODEL - Nanang Susanto; Ariyanto Adi Nugroho; Dwiza Riana; Sri Hadianti (Jurnal TAM (Technology Acceptance Model), 2022)
Competence and knowledge of employees need to be improved continuously. This is in order to improve performance and increase company productivity. This performance indicator becomes difficult to achieve during the COVID-19 pandemic. Microsoft Stream e-Learning was chosen as a solution to continue carrying out competency improvement activities. This study aims to understand the factors that influence employee attitudes towards e-Learning. There were 138 employees who participated in the survey conducted by the researcher. This study applies the Unified Theory of Acceptance and Use of Technology (UTAUT) method with variables including Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavioral Intention to use, Gender, Age, Instructor Quality, and Support System Quality. The test results from the study show a positive and significant effect on the use of Microsoft Stream e-learning with learning facilities, the quality of the instructor and the quality of the support system.